Topical Delivery of Emulsomal Gel for the Management of Skin Cancer (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: The aim of the present study was to develop and characterize lipid vesicular gel for managing skincancer through topical route, because on the delivery of intact drug molecule, it distributed between normalcell and cancerous cell, leading to unacceptable side effects and also require high dose of drug to treat.Materials and Methods: Developed gel base with varying concentration of polymers and prepared emulsomeswas incorporated in gel base, and then, emulsomal gel was evaluated for different parameters such as pHdetermination, viscosity, spreadability, homogeneity, and stability studies. The optimized emulsomal gel wasdone for their in vitro and in vivo drug release study. Results: The optimization of gel base was performedfor different concentrations of Carbopol 934, methyl paraben sodium, glycerine, polyethylene glycol, and PVP.Emulsomal gel was prepared by distribution of emulsomes into the gel base. Physical analysis demonstrated thatthe resulting emulsomal gel had a light yellow color and was uniform and smooth when applied. The optimizedemulsomal gel formulations were shown to be appropriate for all other characterization parameters, such as pH,viscosity, spreadability, and homogeneity. The in vitro drug release study investigation was revealed an improvedemulsomal gel, showed a sustained profile over a 12 h period. Stability studies of emulsomal gel in terms ofresidual drug content and particle size indicated that at 25 ± 2°C temperature formulation,